How does mountain tourism affect green consumption in mount bromo through the lens of memorable mountain tourism experiences? - Salsabil, Achmad; Roostika, R. R. Ratna (Enrichment : Journal of Management, 2024)
The purpose of this research is to investigate the connection between mountain tourism affecting green consumption in Mount Bromo through the lens of memorable mountain tourism experiences. The respondents of this study were the local people of Indonesia who have visited Mountain Bromo with a minimum age of 17th years old. The data information for this study was gathered via an online questionnaire created using Google Forms and completed by 225 participants. The collected data was then analyzed using the Structural Equation Modelling technique via Smart-PLS. According to the study findings, an improved mountain tourism experience can augment the propensity for green consumption in Bromo. Simultaneously, the research highlights the criticality of memorable mountain-based tourism experiences, a profound connectedness with nature, and amplified environmental awareness. These elements are identified to serve as comprehensive mediators in the perpetual association between mountain tourism experience and green consumption. These findings emphasize the potential of mountain tourism as a catalyst for promoting sustainable consumption practices